A novel biological role for the phospholipid lysophosphatidylinositol in nociceptive sensitization via activation of diverse G-protein signalling pathways in sensory nerves in vivo - Gangadharan, Vijayan; Selvaraj, Deepitha; Kurejova, Martina; Njoo, Christian; Gritsch, Simon; Škoricová, Dagmar; Horstmann, Heinz; Offermanns, Stefan; Brown, Andrew J.; Kuner, Thomas; Tappe-Theodor, Anke; Kuner, Rohini (Pain, 2013)
Summary - Lysophosphatidylinositol (LPI) is a novel regulator of peripheral sensory neuron function and pathological pain. The roles of GPCR and non-GPCR components to the biological function of LPI are delineated. - The rich diversity of lipids and the specific signalling pathways they recruit provides tremendous scope for modulation of biological functions. Lysophosphatidylinositol (LPI) is emerging as a key modulator of cell proliferation, migration, and function, and holds important pathophysiological implications due to its high levels in diseased tissues, such as in cancer. Here we report a novel role for LPI in sensitization of peripheral sensory neurons, which was evident as exaggerated sensitivity to painful and innocuous pressure. Histopathological analyses indicated lack of involvement of myelin pathology and immune cell recruitment by LPI. Using pharmacological and conditional genetic tools in mice, we delineated receptor-mediated from non-receptor-mediated effects of LPI and we observed that GPR55, which functions as an LPI receptor when heterologously expressed in mammalian cells, only partially mediates LPI-induced actions in the context of pain sensitization in vivo; we demonstrate that, in vivo, LPI functions by activating Gα13 as well as Gαq/11 arms of G-protein signalling in sensory neurons. This study thus reports a novel pathophysiological function for LPI and elucidates underlying molecular mechanisms.
Gesehen am 05.03.2021